Exploring how trends in Nigerian popular gospel music shape religious pedagogy - Agbo, Benedict (Practical theology, 2023)
This article explores how trends in contemporary Nigerian popular gospel music shape religious pedagogy. By drawing on ethnographic data as well as situating popular music creative and stylistic dispositions within theological discourses, we present evidence of convergence between the sacred and popular culture to reveal both engaging and emerging ways for communicating theological truths in Nigeria. We note that the bearers of religion in Nigeria appropriate ideas within the existing and fragmented religious traditions/authorities and also fuse them up using approaches of appropriation, which are broadly garnered from the country’s popular music practices and industries. Consequently, we argue for a theological renaissance wherein scholars may wish to reappraise the significance of specific approaches to popular gospel music for the purpose of evangelism in the Nigerian churches.